Proteinuria as a Critical Indicator of Kidney Dysfunction in Type 2 Diabetes Patients: Insights From a Cross-Sectional Study - Kiconco, Ritah; Okoboi, Joash; Mwesige, Samuel; Muwonge, Kizito; Kinobe, Robert; Kalyesubula, Robert; Kiwanuka, Gertrude N. (Cureus, 2024)
Background: Kidney dysfunction is a common finding among patients with diabetes mellitus. We sought to determine the prevalence and contributors to kidney dysfunction among type 2 diabetes mellitus (T2D) patients. Methods: In this descriptive and analytical cross-sectional study, we received consent and enrolled 148 T2D patients attending the diabetic clinic of Soroti Regional Referral Hospital in eastern Uganda from May 2023 to July 2023. We used questionnaires to obtain participants’ socio-demographic and behavioral characteristics. Blood and urine samples were collected and analyzed for kidney dysfunction and other metabolic biomarkers, which included serum glucose, creatinine, estimated glomerular filtration rate (eGFR), blood urea nitrogen (BUN), uric acid, triglycerides, total cholesterol, low and high-density lipoprotein cholesterol, and urinalysis. We performed blood tests using an automated chemistry analyzer. Results: Of the 148 participants with T2D, 71 (47.97%) had kidney dysfunction (95% CI: 39.98-56.07). Bivariate and multivariate logistic regression analysis revealed only total proteinuria (OR 1.046; 95% CI: 1.014-1.079; P = 0.004) as a significant factor contributing to the observed kidney dysfunction in T2D patients. Conclusion: Kidney dysfunction is a common occurrence among T2D patients in our study setting. The presence of proteins in urine contributes immensely to the observed kidney status in our study population. Total proteinuria should be frequently screened in the routine care of T2D patients in eastern Uganda to curb kidney dysfunction at an early stage. Also, a larger study is recommended to validate these findings and inform screening programs in the study area.
Keywords: Urinalysis; Screening tests; Biomarkers; Hyperuricemia; Proteinuria